2020
DOI: 10.2147/idr.s282880
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Nasal Colonization in Spanish Children. The COSACO Nationwide Surveillance Study

Abstract: Objective To assess the prevalence and risk factors for S. aureus and methicillin-resistant S. aureus (MRSA) nasal colonization in Spanish children. Methods Cross-sectional study of patients <14 years from primary care centers all over Spain. Clinical data and nasal aspirates were collected from March to July 2018. Results A total of 1876 patients were enrolled. Prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…The MRSA colonisation rates observed (2%) are similar to those reported in our previous community studies (1.4%) 9 , highlighting the fact that MRSA is not currently a relevant issue among children in Spain. A number of authors have also reported that, in children with CCCs, infections are mostly caused by Enterobacteriaceae and Pseudomonas , while S. aureus has a less relevant role 36 , 37 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The MRSA colonisation rates observed (2%) are similar to those reported in our previous community studies (1.4%) 9 , highlighting the fact that MRSA is not currently a relevant issue among children in Spain. A number of authors have also reported that, in children with CCCs, infections are mostly caused by Enterobacteriaceae and Pseudomonas , while S. aureus has a less relevant role 36 , 37 .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of S. aureus colonisation in this series (16%) is below the 33% reported in community-dwelling children in Spain 9 , although our included patients were young, and the prevalence of colonization is usually increased in older children 7 , 9 . However, as we have analyzed children with CCCs, a higher rate of carriage status were expected to be found, at least for MRSA strains, compared to children from the community, as other authors have reported higher colonization rates of S. aureus and MRSA in chronically institutionalized children 7 .…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…4 In Spain there are practically no available data on resistance to fusidic acid or mupirocin in outpatients, although recent data in children under 14 years of age which were nasal carriers showed a 2.2% of resistance to fusidic acid in S. aureus and 5.6% in MRSA16 and a 7% resistance to mupirocin in S. aureus and a 4% in MRSA. 17 The development of ozenoxacin followed the requirements for the development of new antibiotics for skin infections published in the FDA 2010 Guidance for Industry 18 . In this guidance, only impetigo is considered as a primary infection with enough entity to demonstrate the efficacy and Accepted paper safety of topical antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%